Factors Influencing Green Human Capital to Improve Green Performance in Indonesian Start-Up Business - Ina Ratnamiasih; Mochammad Ridwan; Budi Septiawan (Indonesian Journal of Sustainability Accounting and Management, 2022)
This study gathers empirical evidence on the influence of green human resource management, green training, and the role of government in encouraging green human capital to improve green performance. The author conducted this study using a survey of 91 startup businesses in Indonesia as the sample, selected using a purposive sampling method. Data were collected using questionnaires. After collection, the author tested the validity and reliability of the data prior to hypotheses testing. Data analysis for hypothesis testing adopted partial least squares regression. Results indicate that green human capital management, green training, and the role of government significantly affect green human capital. Green human capital in turn significantly affects Green Performance. Green Performance can be successful by increasing awareness of green human capital on the part of startup businesses in Indonesia. Using green human capital to improve green performance will require green human resource management, green training, and the participation of the government, which must carry out its assistance with implementation through a sustainable commitment. Green Performance measurement is an issue of concern for sustainability and environmental balance in startup businesses in Indonesia.